DAMPAK PENGUNGKAPAN SUMBER DAYA MANUSIA TERHADAP REPUTASI PERUSAHAAN - Rachmatika Pramuna M P; Surya Raharja (Diponegoro Journal of Accounting, 2013)
The purpose of this research is to analyze the effects of human resource disclosure on corporate image. This study attempts to examine it with 1 independent variable (human resource disclosure) and 5 control variables such as : corporate size, leverage, ROA, type of industry and ownership concentration. This research is an empirical study with purposive sampling techniques in collecting data. The population is 133 companies listed in Indonesian Corporate Image Amard 2012 with excellent result. The data obtained from secondary data on the annual report of non-financial companies in 2011. After reduces with several criteria, 48 companies non-financial are determined as research samples. The analysis technique in this study uses a linear regression analysis with help from a program named SPSS. The result indicates that human resource disclosure is significantly influence on corporate image. Furthermore, control variabels like corporate size and ROA are signicantly influence on corporate image but leverage, type of industry and ownership conscentration are does not significantly influence on corporate image.